1989
DOI: 10.1021/ac00185a012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relative role of Penning ionization in low-pressure glow discharges

Abstract: Optical Investigations Into the relative role of Penning Ionization as a mechanism for the Ionization of sputtered species In low-pressure argon glow discharges were carried out. These studies employed methane as a quenching agent to effectively reduce the argon metastable population. This reduction of metastable atoms significantly limits the extent of Penning Ionization present In the discharge, which will decrease ion emission signals from the sputtered species. The magnitude of the decrease In these Ion em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…The result is that charge transfer can be very efficient for the ionization of molecular species in the plasma. Penning ionization, on the other hand, is negligible at pressures lower than 0.3 torr [21]. This explains the low population of the distribution in the 8 -12 eV energy range.…”
Section: Parametric Effects On P()mentioning
confidence: 94%
See 2 more Smart Citations
“…The result is that charge transfer can be very efficient for the ionization of molecular species in the plasma. Penning ionization, on the other hand, is negligible at pressures lower than 0.3 torr [21]. This explains the low population of the distribution in the 8 -12 eV energy range.…”
Section: Parametric Effects On P()mentioning
confidence: 94%
“…Penning ionization is a major ionization mechanism for species with ionization potentials lower than the energy level of metastable argon atoms. Smith et al observed that in the steady state plasma, Penning ionization accounts for 40 -80% of the ionization of sputtered species [21]; it is thus expected to play an important role in W(CO) 6 ionization and excitation as well. Charge transfer processes of Ar ϩ with W(CO) 6 result in an energy distribution between 13 to 20 eV with the maximum around argon's ionization potential at ϳ15 eV [20].…”
Section: Temporal Characteristics Of P() Over a Pulse Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…[24] It has been shown that Penning ionisation accounts for 40-80% of the total sputtered atom ionisation occurring in a GD source. [25] The maximum of the argon metastable population is therefore determined by the time required for the electrons to thermalise. The enhanced 181 Ta + signal in the afterglow follows the second Ar peak of the afterglow, indicating ion formation through Penning ionisation processes.…”
Section: Time-resolved Detection Mode In Rf Glow Discharge Mass Spectmentioning
confidence: 99%
“…80% of all sputtered atom ionization in analytical glow discharges plasmas. 10 In argon, the metastable states of 3 P 2 and 3 P 0 occur with energies at 11.52 eV and 11.72 eV. This energy is great enough to ionize a majority of the elements within the Periodic Table without ionizing may of the atmospheric impurities present in the discharge.…”
Section: Excitation and Ionization Processesmentioning
confidence: 99%